Modelling the hydrological behaviour of a coffee agroforestry basin in Costa Rica - Gómez Delgado, F; Roupsard, O.; Maire, G. le; Taugourdeau, S.; Pérez, A.; Oijen, M. van; Vaast, P.; Rapidel, B.; Harmand, J.M.; Voltz, M.; Bonnefond, J.M; Imbach, Pablo A.; et al. (2015)
The profitability of hydropower in Costa Rica is affected by soil erosion and sedimentation in dam reservoirs, which are in turn influenced by land use, infiltration and aquifer interactions with surface water. In order to foster the provision and payment for Hydrological Environmental Services (HES), a quantitative assessment of the impact of specific land uses on the functioning of drainage-basins is required. The present paper aims to study the water balance partitioning in a volcanic coffee agroforestry microbasin (1 km2, steep slopes) in Costa Rica, as a first step towards evaluating sediment or contaminant loads. The main hydrological processes were monitored during one year, using flume, eddy-covariance flux tower, soil water profiles and piezometers. A new Hydro-SVAT lumped model is proposed, that balances SVAT (Soil Vegetation Atmosphere Transfer) and basin-reservoir routines. The purpose of such a coupling was to achieve a trade-off between the expected performance of ecophysiological and hydrological models, which are often employed separately and at different spatial scales, either the plot or the basin. The calibration of the model to perform streamflow yielded a Nash-Sutcliffe (NS) coefficient equal to 0.89 for the year 2009, while the validation of the water balance partitioning was consistent with the independent measurements of actual evapotranspiration (R2 = 0.79, energy balance closed independently), soil water content (R2 = 0.35) and water table level (R2 = 0.84). Eight months of data from 2010 were used to validate modelled streamflow, resulting in a NS = 0.75. An uncertainty analysis showed that the streamflow modelling was precise for nearly every time step, while a sensitivity analysis revealed which parameters mostly affected model precision, depending on the season. It was observed that 64% of the incident rainfall R flowed out of the basin as streamflow and 25% as evapotranspiration, while the remaining 11% is probably explained by deep percolation, measurement errors and/or inter-annual changes in soil and aquifer water stocks. The model indicated an interception loss equal to 4% of R, a surface runoff of 4% and an infiltration component of 92%. The modelled streamflow was constituted by 87% of baseflow originating from the aquifer, 7% of subsurface nonsaturated runoff and 6% of surface runoff. Given the low surface runoff observed under the current physical conditions (andisol) and management practices (no tillage, planted trees, bare soil kept by weeding), this agroforestry system on a volcanic soil demonstrated potential to provide valuable HES, such as a reduced superficial displacement-capacity for fertilizers, pesticides and sediments, as well as a streamflow regulation function provided by the highly efficient mechanisms of aquifer recharge and discharge. The proposed combination of experimentation and modelling across ecophysiological and hydrological approaches proved to be useful to account for the behaviour of a given basin, so that it can be applied to compare HES provision for different regions or management alternatives.